Too Little or Too Much? Actionable Advice in an Early-Childhood Text Messaging Experiment - Kalena E. Cortes; Hans Fricke; Susanna Loeb; David S. Song (Institute of Labor Economics (IZA), 2018)
Text-message based parenting programs have proven successful in improving parental engagement and preschoolers' literacy development. The tested programs have provided a combination of (a) general information about important literacy skills, (b) actionable advice (i.e., specific examples of such activities), and (c) encouragement. The regularity of the texts – each week throughout the school year – also provided nudges to focus parents' attention on their children. This study seeks to identify mechanisms of the overall effect of such programs. It investigates whether the actionable advice alone drives previous study's results and whether additional texts of actionable advice improve program effectiveness. The findings provide evidence that text messaging programs can supply too little or too much information. A single text per week is not as effective at improving parenting practices as a set of three texts that also include information and encouragement, but a set of five texts with additional actionable advice is also not as effective as the three-text approach. The results on children's literacy development depend strongly on the child's pre-intervention literacy skills. For children in the lowest quarter of the pretreatment literacy assessments, only providing one example of an activity decreases literacy scores by 0.15 standard deviations relative to the original intervention. Literacy scores of children in higher quarters are marginally higher with only one tip per week. We find no positive effects of increasing to five texts per week.
Keywords: I21; I24; J18; 330; text messaging; parental engagement; literacy and reading skills; and parent-child activities